Implementasi Pasar Modal Syariah: Fenomena Saham Syariah Sebagai Isu Kapitalisasi Halal Di Indonesia - Munawiroh, Afifatul; Rumawi, Rumawi (UI Scholars Hub, 2022)
This article is a research-based in a study library reseacrh. The theme raised in this study is Sharia Stocks as an Issue of Halal Capitalization in Indonesia. Sharia stocks are investments in the capital market which are based on Islamic-based rules. Investors in Islamic stocks are not only from Muslims but, non-Muslims can also invest in sharia shares. There are three important questions in this research. First, what is meant by Islamic stocks? Second, how the interaction of investors on Islamic stocks so that it becomes a national capitalization issue? Third, what is the implications of Islamic stocks as a national capitalization issue? With a phenomenology approach to explaining the interaction of investors on Islamic stocks so that it becomes a national capitalization issue and the implications of Islamic stocks as a national capitalization issue. Whereas, the purpose of Islamic stocks is explained in the analysis content approach. The result of this research is that Islamic stocks are one of the most attractive investments for investors because of the principle of justice that is upheld and they can also invest according to personal will because there is no relation to government licensing.